Spatial beam shaping of a focused laser with quasi-near-field characteristics based on a concatenated fuzzy matching algorithm - Zhu, Chengyu; Li, Yuxin; Yuan, Hang; Wang, Yulei; Liang, Lingxi; Sun, Xin; Wang, Wenjie (Optik (Stuttgart), 2021)
We demonstrate a concatenated fuzzy matching algorithm to restrain local strong regions for the spatial beam shaping of a focused laser with quasi-near-field characteristics on the cross section in the focusing light path. Considering that the light field is redistributed according to the spatial angular spectrum after the laser beam is converged, modulations increasing with the propagation distance will decrease the smoothness of the beam. An effective algorithm for the spatial beam shaping of such focused laser is discussed by establishing the cascaded correspondence between the light field in the front stage and the later stage. The results show that the fluence contrast reduces from 37.2% to 21.4%, and the intensity modulation from 3.33:1–1.86:1. Meanwhile, the low-frequency components corresponding to local large-scale strong regions of the light field in the PSD distribution are effectively suppressed. A more regular spatial intensity profile of the focused laser is finally obtained.